Backlash Over Gender-Fair Language: The Impact of Feminine Job Titles on Men's and Women's Perception of Women. (December 2014) - Budziszewska, Magdalena; Hansen, Karolina; Bilewicz, Michał
Feminine forms of job titles raise great interest in many countries. However, it is still unknown how they shape stereotypical impressions on warmth and competence dimensions among female and male listeners. In an experiment with fictitious job titles men perceived women described with feminine job titles as significantly less warm and marginally less competent than women with masculine job titles, which led to lower willingness to employ them. No such effects were observed among women.